Comparative Efficacy of Platelet-Rich Plasma Dressing Versus Normal Saline Dressing in the Management of Chronic Wounds - Muhammad Kaleem Khan, Farwa Zohaib, Jawad Ahmed, Sarfraz Ahmad, Sidra Abbas, Sadaffasih, Muhammad Hamza Shafi, Fahim Ullah (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Healing times for chronic wounds are prolonged and treatment is often complicated. Platelet rich plasma (PRP) therapy is becoming a viable modality for improving healing of wounds. Objective: To evaluate and compare the efficacy of PRP dressing versus Normal Saline (NS) dressing in terms of healing rates and duration to achieve healing in chronic wounds. Material and Methods: A randomized controlled trial was performed in the Surgical 2 Jinnah hospital Lahore in June to march 2023. A total of 100 patients with chronic wounds participated and were randomly assigned into two groups: The comparison was made between PRP dressing (50 patients) and NS dressing (50 patients). We collected information regarding baseline characteristics including age, wound duration and demographics. Patients were followed weekly for up to six weeks or until their wounds healed. Statistical method was used for healing rates and mean time of healing with p ≤ 0.05. Results: In this study, mean age of patients was 37.54±11.755 and 38.98±11.828 years in PRP and NS group. The mean duration of wounds was 30.28±12.622 weeks for the PRP Dressing group and 29.66±12.748 weeks for the Normal Saline group.The PRP dressing group achieved a statistically significant higher healing rate of 92.0% compared to 68.0% in the NS dressing group (p = 0.003). The mean duration to achieve healing was significantly shorter in the PRP group (1.28±0.882 weeks) compared to the NS group (2.22±1.898 weeks, p = 0.002). Stratified analysis showed that PRP dressing was particularly effective in older patients, chronic wounds of longer duration, and specific wound types (e.g., diabetic wounds). Conclusion: The results indicated that PRP dressing were better than NS dressing for accelerating wound healing and higher success rate used in the management of chronic wounds. Keywords: Chronic wounds, PRP dressing, Normal Saline dressing, Platelet-Rich Plasma, wound healing